2022
DOI: 10.1002/jia2.25985
|View full text |Cite
|
Sign up to set email alerts
|

Non‐communicable diseases by age strata in people living with and without HIV in four African countries

David Chang,
Allahna L. Esber,
Nicole F. Dear
et al.

Abstract: Introduction: Non-communicable diseases (NCDs) are an important driver of morbidity among ageing people living with HIV (PLWH). We examined the composite role of age and HIV status on NCDs in people living with and without HIV. Methods: The African Cohort Study (AFRICOS) prospectively enrols participants aged ≥15 years with and without HIV at 12 sites in Kenya, Tanzania, Uganda and Nigeria. From 21 January 2013 to 1 September 2021, we assessed participants for renal insufficiency (estimated glomerular filtrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…ART effects on lifespans led PLWH to be exposed to NCD risk factors as much as normal people 7 , 16 . The rapid change in demographic characteristics of this population and the epidemiological transition enhanced by unhealthy behaviors such as an unhealthy diet and lower physical activity could increase the chance of NCDs 43 . Hypertension is one of the main cardiovascular disease (CVD) risk factors 44 .…”
Section: Discussionmentioning
confidence: 99%
“…ART effects on lifespans led PLWH to be exposed to NCD risk factors as much as normal people 7 , 16 . The rapid change in demographic characteristics of this population and the epidemiological transition enhanced by unhealthy behaviors such as an unhealthy diet and lower physical activity could increase the chance of NCDs 43 . Hypertension is one of the main cardiovascular disease (CVD) risk factors 44 .…”
Section: Discussionmentioning
confidence: 99%
“…(325 000-429 000) PWH were over age 50, representing 26% (23-29%) of all PWH. Without additional intervention, the median age increased to 43 (39)(40)(41)(42)(43)(44)(45)(46) in 2040, with 479 000 (364 000-600 000) over age 50 (or 34% (26-43%) of all PWH, Fig. 3; Table S3 [26][27][28][29][30][31][32][33][34]) versus women (22 [19-24]).…”
Section: Resultsmentioning
confidence: 99%
“…Additional research in this setting will hopefully lead to a reevaluation of the care needs of African PWH. For instance, recent studies of NCDs among PWH in Africa have found high rates of elevated blood pressure, dysglycemia, renal insufficiency, and obesity [40][41][42][43][44].…”
Section: Sensitivity Analysismentioning
confidence: 99%
“… 9 , 10 , 11 , 12 , 13 , 14 This convergence could be linked to the ageing HIV-positive population in these regions, the associated increasing burden of non-communicable diseases among these individuals, and the hastening effect of HIV on non-communicable disease acquisition. 15 Managing the convergence of diseases is of even greater concern since the beginning of the COVID-19 pandemic because poorly controlled multimorbidity has been associated with an increased risk of severe outcomes from COVID-19. 16 , 17 Moreover, an increase in ageing among people living with HIV as a result of the success of antiretroviral therapy has seen a subsequent increase in non-communicable diseases in this group, resulting in recognition of the need for integrated infectious disease programmes and non-communicable disease care and prevention programmes to avoid a loss of health gains made through antiretroviral therapy.…”
Section: Introductionmentioning
confidence: 99%